Use of Plants in the Religious Traditions of the Wangi-Wangi Community - Balda, Balda; ., Widayanti; La Fua, Jumarddin; Rosmini, Rosmini (KnE Social Sciences, 2022)
This research aimed to examine the types and sustainable use of plants in religious traditions in Wangi-Wangi District, Wakatobi Regency, and to determine the feasibility of using related learning media for biology class X at Madrasah Aliyah 1 Wakatobi. Qualitative descriptive methods were used and data were collected through interviews and observations. The results found that there are 13 plant families of 14 species that are most widely used in these religious traditions. The most widely used plants are two species in the Graminaceae family, while one species from the following families are also used: Arecaceae, Palmae, Musaceae, Crassulaceae, Poaceae, Zingiberaceae, Lytheraceae, Euphorbiaceae, Rubiaceae, Solonaceae, Piperaceae and Malvaceae. The habitat of the area consists of trees, shrubs and herbs. Of the plants that are most widely used in religious traditions, 43% are trees, 36% are herbaceous, and only 21% are shrubs. The parts of plants that are used include flowers, leaves, stems and tubers. 29% of use is of the fruit, 29% is of the leaf and 14% is of the tuber. Only 7% of use is of the stems. Of the sustainable plants, 11 species are cultivated plants (85%) and three species are non-cultivated plants (15%). Keywords: religious traditions, habitus, plants